Quantitative Mineralogical Composition of Calculi and Urine Abnormalities for Calcium Oxalate Stone Formers: A Single-Center Results - Kustov, Andrey V.; Strelnikov, Alexander I. (Urology Journal, 2018)
Purpose: The paper focuses on the relationship of risk factors and metabolic disorders with mineralogical composition of calculi, age and gender of calcium oxalate stone formers. Materials and Methods: Stone mineralogical composition, 24 hour biochemistry and pH-profile of urine were examined for sixty four stone formers using powder X-ray diffraction, spectrophotometric and potentiometric techniques. Results: The analysis indicated that 44 % of calculi were composed of pure calcium oxalate monohydrate, whereas other 56 % contained both monohydrate and dihydrate or usually their mixtures with hydroxyl apatite. Hypocitraturia, hypercalciuria and hyperuricosuria were identified as the most frequent disorders. Patients with pure calcium oxalate stones and calcium oxalate mixed with apatite revealed different patterns including age, acid-base balance of urine, calcium, citrate excretion etc. Conclusions: Our results demonstrate that most patients simultaneously reveal several risk factors. The special attention should be paid to normalize the daily citrate, calcium and urate excretion. High risk patients, such as postmenopausal females or stone formers with a high apatite content require a specific metabolic evaluation towards in highlighting abnormalities associated with stone formation.